Think Global, Invest Responsible: Why the Private Equity Industry Goes Green - Crifo, Patricia (Journal of business ethics, 2013)
The growth of socially responsible investment (SRI) on public financial markets has drawn considerable academic attention over the last decade. Discarding from the previous literature, this article sets up to analyze the Private Equity channel, which is shown to have the potentiality to foster sustainable practices in unlisted companies. The fast integration of the environmental, social and governance issues by mainstream Private Equity investors is unveiled and appears to have benefited from the maturation of SRI on public financial markets and the impetus of large conventional actors. Hypotheses on the characteristics and drivers of this movement are proposed and tested on a unique database covering the French Private Equity industry in 2011. Empirical findings support that Private Equity socially responsible investing is characterized by investor engagement and strategically driven by a need for new value creation sources, increased risk management and differentiation. In particular, results show that independent funds, which need to attract investors, are more likely than captive funds to develop socially responsible practices. Evolution of the movement and future research paths are proposed.